All Days 1983
DOI: 10.4043/4501-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using the Pressuremeter Curve To Design Laterally Loaded Piles

Abstract: The~-y curve is a soil model used in the design of laterally loaded piles. A method is presented to obtain the P-y curve from the pressuremeter curve. This method distinguishes between the friction model and the front resistance model. Using this approach, comparisons are made between the predicted and measured behavior of two laterally loaded piles; one in a soft clay and one in a medium to dense sand. The comparisons show very good agreement and point out that a distinction may have to be made between displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…When scaling to large-diameter piles, a distinction must be made between a pile that behaves in an almost rigid fashion and one that is relatively flexible, since this affects the soil-pile behaviour (Briaud et al, 1984). A rigid pile rotates without flexing significantly, and develops a 'toe kick' under moment and lateral loading.…”
Section: Shortcomings Of Current Methodologymentioning
confidence: 99%
“…When scaling to large-diameter piles, a distinction must be made between a pile that behaves in an almost rigid fashion and one that is relatively flexible, since this affects the soil-pile behaviour (Briaud et al, 1984). A rigid pile rotates without flexing significantly, and develops a 'toe kick' under moment and lateral loading.…”
Section: Shortcomings Of Current Methodologymentioning
confidence: 99%
“…According to the author, this method is recommended to the design of drilled piers supporting transmission line structures. Briaud et al (1985) The total lateral reaction P to the deflection Y at a given depth is the sum of the frontal reaction Q and the tangential reaction F. As a result, the P-Y is the addition of the Q-Y curve and the F-Y curve. Carayannacon et al (1979) showed by finite element analysis that the contribution of the tangential reaction increases with slenderness of the pile section.…”
Section: Methods Of Dunand (1981)mentioning
confidence: 99%
“…no slurry. Among the previous studies of laterally loaded drilled shafts which have utilized soil pressure cells (Kasch et al 1977and Briaud et al 1983, 1985, the work by Bierschwale et al (1981) is of particular interest because the pressure cell data are well documented, and data for several azimuthal angles relative to the direction of loading are available.…”
Section: Previous Studies Of Interface Stressesmentioning
confidence: 99%